Republic of Estonia : 2022 Article IV Consultation-Press Release; Staff Report; and Statement by the Executive Director for the Republic of Estonia. - International Monetary Fund. European Dept. (Washington, D.C. : International Monetary Fund, 2022)
Estonia's economy is vulnerable to the fallout from the war in Ukraine given its geographical proximity to Russia, the geopolitical context, and high passthrough from global energy prices to domestic inflation. Although direct exposures to Russia and Ukraine through trade, services, and financial channels appear to be contained, the war is already significantly affecting economic confidence. Nevertheless, economic activity has progressively adapted to the pandemic, rebounding strongly in 2021, and as of mid-2022, remaining resilient to the headwinds from the war. Inflation has surged into double digits and is increasingly broad-based.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet
Keywords: International Agreements and Observance; International Organizations; Monetary Policy; Estonia, Republic of